Japanese and Indonesian Prohibitive Expressions on Prohibition Signs at Train Stations: A Linguistic Landscape Study - Afifah, Muthi (Universitas Pendidikan Indonesia (Indonesia University of Education), 2022)
This article focuses on the expressions of prohibition signs in Japan and Indonesia. Based on the Politeness Theory of Brown Levinson (1987), consideration for the other conversation participants is expected if the speaker tells them not to do something in personal communication. In contrast, the expressions on prohibition signs in public spaces did not need such consideration and can be done “without redressive, baldly”. However, many prohibitions signs use polite expressions. Japanese has “keigo” system that adjusts the usage of vocabulary depending on whom the listener is, while Indonesian does not have that system although polite expression is commonly used. This article aims to resolve those differences and compares the expression of prohibitions signs, especially in train stations, which displayed many prohibited signs from cautions, and manners expressions. The data in this study were collected at Tokyo station-Tokyo and Osaka station-Osaka in Japan, and Gambir station-Jakarta and Gubeng station-Surabaya in Indonesia. The results found that the prohibition signs at railway stations in Indonesia used prohibitive expressions with and without honorific expressions almost equally. On the other hand, Japan’s railway stations used more prohibitive expressions with honorifics on their prohibition signs. In Japan railway stations, the use of honorific expressions on prohibition signs is part of their service and to appeal that they are a railway company with good service.